Animal Immanence: Review of Felice Cimatti and Carlo Salzani, eds. Animality in Contemporary Italian Philosophy - Amberson, Deborah (Humanimalia, 2022)
Review of Felice Cimatti and Carlo Salzani, eds., Animality in Contemporary Italian Philosophy (Cham: Palgrave Macmillan, 2020)